T4 stage and preoperative anemia as prognostic factors for the patients with colon cancer treated with adjuvant FOLFOX chemotherapy - An, Min Sung (World J Surg Oncol, 2015)
BACKGROUND: FOLFOX-based adjuvant chemotherapy is a benefit for high-risk stage II and stage III colon cancer after curative resection. But, the prognostic factor or predictive marker for the efficacy of FOLFOX remains unclear. This study was aimed to identify the prognostic value and cumulative impact of adjuvant FOLFOX on the stage II and III colon cancer patients. METHODS: A total of 196 stage II and III colon cancer patients were retrospectively enrolled in prospectively collected data. They underwent curative resection followed by FOLFOX4 adjuvant chemotherapy. The oncological outcomes included the 5-year disease-free survival (DFS) rate and 5-year overall survival (OS) rate. Cox-regression analysis was performed to identify the prognostic value, and its cumulative impact was analyzed. RESULTS: The 5-year DFS rate of the patients was 71.94% and the 5-year OS rate was 81.5%. The prognostic values for the 5-year DFS rate and 5-year OS rate were T4 stage and preoperative anemia in a multivariate analysis. Each patient group who had no prognostic value, single, or both factors revealed 95.35%, 69.06%, and 28.57% in the 5-year DFS rate, respectively (p < 0.0001). The 5-year OS rate also showed the significant differences in each group who had no prognostic value, single, or both factors revealed 100%, 79.3%, and 45.92%, respectively (p < 0.0001). CONCLUSION: Our results showed similar efficacy to MOSAIC study in stage II and stage III colon cancer patients treated with adjuvant FOLFOX chemotherapy after curative resection. Patients who had T4 stage and/or preoperative anemia showed worse prognosis than patients without any prognostic value. These findings suggest that FOLFOX could not be effective in the patients with T4 stage colon cancer accompanied by preoperative anemia.